2021
DOI: 10.1038/s41598-020-80190-8
|View full text |Cite
|
Sign up to set email alerts
|

Speech adapts to differences in dentition within and across populations

Abstract: We test the hypothesis that a specific anatomical feature, the dental malocclusion associated with reduced dental wear, causes languages to adapt by relying more heavily on labiodental consonants. In contrast to previous work on this topic, we adopt a usage-based approach that directly examines the relative frequency of such labiodental sounds within phonetically transcribed word lists and texts from thousands of languages. Labiodentals are shown to be very infrequent in the languages of hunter gatherers, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…Most critically, perhaps, it was demonstrated that labiodentals are notably lacking in the phoneme inventories of contemporary hunter–gatherer populations. In follow-up work, the hypothesis was tested with frequency-based data [34]. It was found that labiodental consonants represent about 2% of all consonants in the word lists of agricultural populations but are nearly absent in the word lists of hunter–gatherers.…”
Section: Consonantsmentioning
confidence: 99%
“…Most critically, perhaps, it was demonstrated that labiodentals are notably lacking in the phoneme inventories of contemporary hunter–gatherer populations. In follow-up work, the hypothesis was tested with frequency-based data [34]. It was found that labiodental consonants represent about 2% of all consonants in the word lists of agricultural populations but are nearly absent in the word lists of hunter–gatherers.…”
Section: Consonantsmentioning
confidence: 99%
“…The production of such prefixes actually varies across individuals with distinct bite types, at least in some cases. Some of the individuals we observed in Everett & Chen (2021) do not actually produce [im-] with a bilabial nasal but with a labiodental nasal. Now let us imagine that in a given population the amount of people that produce bilabial nasals as labiodentals is 2%, but in another it is 20% given clear disparities in overbite/overjet prevalence across populations.…”
Section: How "External" Factors Are Compatible With Our Understandingmentioning
confidence: 90%
“…In response to Blasi et al (2019), some suggested that well-established lenition processes, principally the lenition of /p/ to /f/, are sufficient to account for the global distribution of labiodentals observed in that study. While we know that lenition is common crosslinguistically, however, a lenition-based account alone could not in principle explain the typological distributions noted by Blasi et al (2019) or Everett & Chen (2021). A key question is whether certain bite types cause such lenition to be more prevalent in populations with overbite/overjet.…”
Section: How "External" Factors Are Compatible With Our Understandingmentioning
confidence: 95%
See 2 more Smart Citations